Evaluación del impacto de los microcréditos al desarrollo empresarial de microempresas del Cantón Calvas 2019-2022 - Palacios Aymar, María José (2023)
The objective of this research was to determine the impact of microcredits on the entrepreneurial development of microenterprises in Calvas during the period 2019-2022. Microcredits are conceived as a tool designed to facilitate access to project financing, with the purpose of improving, building, and supporting the necessary conditions for sound business development. Therefore, this study becomes relevant as it seeks to understand the impact of microcredits in this context. To address this objective, a mixed approach was used, combining exploratory, descriptive, and explanatory research. A literature review was conducted, and information was gathered through surveys applied to a sample of 28 organizations. From this information, a relationship between the credit amount and the indicators of business development, such as assets, income, number of employees, and company value, was established. This was achieved through simple linear regression econometric models, along with representing the relationships between variables using Ishikawa diagrams. The findings of the study indicate that while microenterprises generally access microcredits, they do not always achieve their intended purpose. Furthermore, it was concluded that the growth indicators of microenterprises are not directly linked to the amount of the microcredit but can depend on external factors such as the economic recovery following the COVID-19 health crisis, as well as internal factors like the management and administration of financing in each microenterprise. Therefore, microcredits are considered to be a beneficial financing tool for micro-entrepreneurs, provided they are prepared to handle unforeseen situations and manage their resources adequately.